Preoperative design of expansive open-door laminoplasty: A computer-assisted morphometric analysis. (29th July 2013) - Li, Ang; Wang, Qian; Gao, Yang; Yang, Jing; Wang, Yu; Li, Xin-Kui
Abstract: Whereas the expansive open-door laminoplasty (EL) has been applied widely and the bone gutter on the hinge side is essential for EL, little is known regarding the mandatory width of the bone gutter. This study addressed the essential parameters of bone gutters for EL. Preoperative axial CT images of 20 patients suffering from cervical myelopathy were downloaded and entered into a computer. EL was then simulated using a computer-assisted technique and the thickness of the laminae at the gutter sites was measured. Accordingly, the width of the bone gutter was linked mathematically with the angle of the lifted lamina and the thickness of the lamina at the lamina-lateral mass junction. Furthermore, the average thickness of the laminae at the gutter site was 6.19 mm, and the appropriate bone gutter for EL was 5.13 to 7.15 mm. The width of the bone gutter can thus be planned precisely preoperatively, which may help improve the safety and accuracy of expansive open-door laminoplasty.